Problem-based learning: 'One for All and All for One' / Lim Wai Fun - Lim, Wai Fun
Problem based Learning (PBL) is Learner Driven Learning that engages students to learn domain knowledge to solve real world problems in groups. Group work is not an option in PBL but in reflective journals, some students expressed a lot of frustration at having to work with others as with a student who lamented that "I didn't even realize he was one of our group members until the day of our presentation". From a PBL practitioners' point of view, the researcher views with frustration the situation where a single uncooperative group member can affect group learning and the success of the completion of their PBL projects. An informal questionnaire given to 58 students indicate mixed opinions regarding working in groups. All of them do not deny the benefits of group work over the lecture mode of teaching but many indicate a preference for working individually. The results indicate a need for PBL practitioners to monitor group performance during the PBL learning process outside of class time. Monitoring forms for the 3 stages of the PBL process: the group meeting at the problem stage (Form#1), the individual researching stage (Form#2), and finally, the group leader's report (Form#3). Reading the forms allowed the researcher, as the PBL facilitator, to provide feedback, ask questions, reprimand slackers and praise those working well.